Reprogramming oxidative phosphorylation in cancer - Cuezva, José (Henry Stewart Talks, 2018)
Overview of oxidative phosphorylation, ATP synthase and its regulation by IF1, Functions of ATP synthase/hydrolase in cancer, Aerobic glycolysis and cellular proliferation status, Metabolic reprogramming in proliferation, mRNA binding proteins in translation silencing & cancer progression, Overexpression of IF1 in cancer